Perception of Official Corruption, Satisfaction With Government Performance, and Subjective Wellbeing—An Empirical Study From China - Ma, Jiazheng; Guo, Bin; Yu, Yanghang (Frontiers in Psychology, 2022)
Government factors can have great impacts on people’s happiness, and perceived official corruption undermines perceived government performance. This study aims to examine the link between perceived official corruption and subjective well-being in the context of China and whether satisfaction with government performance has a mediating effect in the process. Based on data from China General Social Survey (CGSS) 2015, a structural equation model was used to test the hypotheses. The results of 3033 Chinese respondents suggest that perception of official corruption is negatively related to subjective well-being, and satisfaction with government performance plays a mediating role in the relationship between perception of official corruption and subjective well-being.